Magic user : reborn in another world as a Max Level Wizard. Novel 1 - Souhei, Mikawa (Seven Seas Entertainment, 2020)
A hardworking salaryman by day immerses himself on weekends in the pen-and-paper roleplaying game Dungeons & Braves, where he plays his favorite character: a max level wizard. When his real life abruptly ends, he is given a second chance as Geo Margilus, his magic user from the game. The powers, wealth, and enchanted loot that he gathered across endless hours of imaginary adventures are now made real. The catch? He's transported to the world of Sedia, a fantasy realm where evil abounds, and ravenous daemons threaten mankind.